2016
DOI: 10.1111/jocs.12698
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Late Retrograde Type A Aortic Dissection After TEVAR: Causes and Management

Abstract: One of the most feared complications of thoracic endovascular aortic repair (TEVAR) and hybrid arch repair is retrograde type A aortic dissection (RTAD). More than two-thirds of RTAD occurs in the immediate postoperative period and first postoperative month. In presentations beyond that point, progression of the native aortopathy must be considered. We report a late presentation of an RTAD seven months after hybrid repair of an aortic intramural hematoma with an ulcer-like projection, and review the causes and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…All RTADs developed in patients who had undergone hybrid repair for chronic dissection. Mosquera et al 11 reported a similar case of late RTAD at 7 months after hybrid arch repair for type B intramural hematoma. Therefore, careful follow-up for late RTAD seems to be more necessary in patients undergoing hybrid arch repair for dissection pathologies.…”
Section: Discussionmentioning
confidence: 91%
“…All RTADs developed in patients who had undergone hybrid repair for chronic dissection. Mosquera et al 11 reported a similar case of late RTAD at 7 months after hybrid arch repair for type B intramural hematoma. Therefore, careful follow-up for late RTAD seems to be more necessary in patients undergoing hybrid arch repair for dissection pathologies.…”
Section: Discussionmentioning
confidence: 91%
“…To achieve reliable anastomosis in our patient, removing the proximal portion of the endograft including cutting the proximal parts of the bare metal stents with metal hooks was necessary to allow mobilization of the anastomotic site, closure the entry tear, and facilitate secure suturing because the ascending aorta was stiff and fixed within the chimney graft. 8 ) Although concerns have emerged regarding the risk of postoperative type 1a endoleak in patients with chimney grafts, this has not occurred during follow-up for 3 years. The main stent was a 40 mm Gore-TAG and it was tightly anastomosed to a 30 mm Dacron graft by tapering the proximal stent, probably leading to close adhesion to the aortic wall that prevented type 1 endoleak ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde dissection from a type B aortic dissection usually involves the transverse arch and its branches and may also involve the ascending aorta following thoracic endovascular aortic repair . We present images of an acute dissection of the pulmonary artery (PA) caused by retrograde extension of an acute type B aortic dissection through a closed ductus arteriosus (DA).…”
mentioning
confidence: 99%